Toṅʻ tanʻʺ sāsanā pru Cha rā toʻ ʼA rhaṅʻ Ūʺ Uttamasāra e* Saṃsarā vatʻ kui lvatʻ ʼoṅʻ runʻʺ kra cuiʹ raiʹ - Uttamasāra, Ūʺ, 1911- (ʼA suiṅʻʺ ʼA vuiṅʻʺ Cā pe : Phranʻʹ khyi reʺ, Rvhe La Vaṅʻʺ Cā pe, 1994)
Teachings of a Burmese Buddhist priest on the cycle of rebirth.